2015
DOI: 10.1161/circimaging.114.003085
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Noninvasive Quantification of Central Venous Pressure by Ultrasound

Abstract: Background— The central venous pressure (CVP) is essential for assessing the cardiac preload and circulating blood volume in clinic. The invasive CVP measurement by central venous catheter has been reported with various complications. The aim of this study was to develop a new noninvasive method for quantification of CVP by ultrasound. Methods and Results— Seventy-six patients who had their CVP monitored for intraoperative or postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Therefore, we compared the ultrasonographic measurement of the collapsing point of the IJV and the invasive measurement of CVP via the conventional column filled up with a 5% sucrose solution. As in recent ICU studies, we found a close relationship between CVPni and CVPi. Our preliminary results suggest that CVPni may be considered as an easily reproducible and reliable method to evaluate and monitor blood volume in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, we compared the ultrasonographic measurement of the collapsing point of the IJV and the invasive measurement of CVP via the conventional column filled up with a 5% sucrose solution. As in recent ICU studies, we found a close relationship between CVPni and CVPi. Our preliminary results suggest that CVPni may be considered as an easily reproducible and reliable method to evaluate and monitor blood volume in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, CVPni is a noninvasive method that can be easily used in daily clinical practice. Thanks to the democratization of compact ultrasound devices in nonspecialized environment, learning the technique became quite easy . The jugular vein remains readily accessible in obese patients, unlike the IVC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xing et al . [ 24 ] reported a new method for noninvasive quantification of CVP, where center of the RA and both cephalic, basilic and brachial veins had a good correlation. Their study showed bias of 0.22 mmHg with LOA of −2.16–2.59 during preoperative measurement which was comparable to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…By adding the noninvasively estimated right ventricular end-diastolic pressure to the end-diastolic PVPG, the pulmonary artery diastolic pressure may be calculated. The right ventricular end-diastolic pressure equals the right atrial diastolic pressure 21 , which can be obtained from the central venous pressure measurement by neck ultrasound 28 . Thus, the noninvasive PVPO method may be clinically useful as a routine assessment of pulmonary artery diastolic pressure.…”
Section: Discussionmentioning
confidence: 99%